Multivessel Disease As A Prognostic Factor For Mortality In STEMI Patients - Kiril Karamfiloff; Kiril Karamfiloff; Petya Georeva; Diana Trendafilova; Julia Jorgova (Journal of Biomedical & Clinical Research)
The main objective of this analysis was to define the influence of multivessel disease involvement compared to single vessel disease on mortality rates in STEMI patients. The retrospective study included 549 patients, hospitalized with STEMI in St. Ekaterina University Hospital (age - 62.66±12.56; women - 31.3%) from 01.06.2008 to 30.06.2011. One-vessel disease was found in 232 patients (44%) as compared to two-vessel disease in 165 patients - 31% and multivessel disease in 130 patients - 25%. There was LM stenosis (>30) in 11 patients (2%); ostial lesion in 33 patients (6.3%); presence of Ca in 37 patients (7%). A stent was implanted in 484 patients (91.8%), and GP IIb/IIIa was used in 400 patients (75.9%). There was significant increase in mortality rates in patients with multivessel disease: 15.6% - 46 patients, compared to one-vessel disease - 6.5% (15 patients) (p